2020
DOI: 10.7554/elife.59889
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin residency determines chromatin loop patterns

Abstract: The organization of chromatin into higher order structures is essential for chromosome segregation, the repair of DNA-damage, and the regulation of gene expression. Using Micro-C XL to detect chromosomal interactions, we observed the pervasive presence of cohesin-dependent loops with defined positions throughout the genome of budding yeast, as seen in mammalian cells. In early S phase, cohesin stably binds to cohesin associated regions (CARs) genome-wide. Subsequently, positioned loops accumulate with CARs at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(114 citation statements)
references
References 105 publications
7
107
0
Order By: Relevance
“…( C ) Peaks of cohesin clusters correlate with previously identified CAR sites. Anti-Mcd1p ChIP-seq trace ( Costantino et al, 2020 ) at chrIII was compared with ChIP-seq traces from Figure 5E . ( D ) ChIP-seq traces showing localization of cohesin clusters on chromosome I (top) and part of chromosome II (bottom).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( C ) Peaks of cohesin clusters correlate with previously identified CAR sites. Anti-Mcd1p ChIP-seq trace ( Costantino et al, 2020 ) at chrIII was compared with ChIP-seq traces from Figure 5E . ( D ) ChIP-seq traces showing localization of cohesin clusters on chromosome I (top) and part of chromosome II (bottom).…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that cohesin forms positioned loops genome-wide in mid-M. These loops continue to form in cells depleted of Pds5p or expressing mcd1p-Q266 where cohesin clustering is blocked ( Costantino et al, 2020 ). The ability of these mutants to loop extrude but not to cluster suggests that cohesin clusters are not obligatory for loop extrusion in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these TAD-like structures and chromatin loops are also found in organisms that lack CTCF homologs. From S.cerevisiae to S.pombe, C.elegans, and A. thaliana, these organisms reveal discrete self-interacting domains with varying domain lengths independent of CTCF (Costantino et al, 2020;Hsieh et al, 2015;Rowley et al, 2017;Rowley and Corces, 2016). The cohesin, a ring-shaped protein complex, mediates the stable cohesion of sister chromatids and loop extrusion by holding distant DNA fragments in close spatial proximity (Murayama et al, 2018;Onn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The nucleolus is the hub of ribosome biogenesis, and aberrant nucleolar morphologies are observed in cohesin depleted models [78,80,81]. In yeast, during mitosis, cohesin was shown to be required for restricting chromatin contacts between rDNA repeats, and between rDNA and the rest of the genome [82]. Cohesin function in facilitating DNA replication appears to be essential for rRNA production and nucleolar integrity [79].…”
Section: Figurementioning
confidence: 99%